Pemanfaatan Komik Sebagai Media Pembelajaran Bahasa Indonesia dalam Meningkatkan Motivasi dan Hasil Belajar Siswa Sekolah Dasar - Mariani, Rika; Novita, Rita; Sari, Siti Mayang (Lembaga Intelektual Muda (LIM) Maluku, 2023)
One of the subjects that is a challenge in providing education in the 21st century is the learning process in Indonesian language subjects. The Indonesian language learning method in class tends to be monotonous using the lecture method, making students easily bored and not understanding the material. On the other hand, the implementation of learning uses illustrated, easy-to-carry and read comic media which can contain text, images and scenes. This can be an alternative medium for learning Indonesian because it stimulates students to be creative, imaginative and innovative, and encourages them to be independent. This research aims to analyze the benefits of using comics as a medium for learning Indonesian to increase student motivation and learning outcomes. This research uses a literature review method with descriptive analysis techniques. Researchers collected data from previous relevant studies within the last ten years. The results of the research that has been carried out illustrate that the use of comic media in learning Indonesian can significantly increase student motivation and learning outcomes